Acute pancreatitis and acute kidney injury in dogs. (March 2019) - Gori, E.; Lippi, I.; Guidi, G.; Perondi, F.; Pierini, A.; Marchetti, V.
Highlights: Clinical severity index evaluation may be a helpful prognostic tool in canine acute pancreatitis. In acute pancreatitis, azotemia and anuria was associated with poor outcome. Acute kidney injury may be a comorbidity of canine acute pancreatitis. Abstract: Acute pancreatitis and acute kidney injury are well-documented comorbidities in human medicine. Dogs that develop acute kidney injury during hospitalization have significantly higher mortality rates than those that do not. The aim of this study was to evaluate the prevalence of acute kidney injury in dogs with acute pancreatitis and the prognostic value of various clinicopathological parameters. Cases of acute pancreatitis presented between January 2012 and June 2016 were identified. The diagnosis of acute pancreatitis was based on two or more of the following clinical signs: abdominal pain, diarrhea, vomiting or anorexia/hyporexia, no other abdominal extra-pancreatic diseases at abdominal ultrasound, and abnormal SNAP cPL test. Diagnosis of acute kidney injury was based on the guidelines of the International Renal Interest Society. Dogs were classified into survivors and non-survivors. Serum creatinine, urea, amylase, total calcium, total cholesterol, C-reactive protein, WBC and band neutrophils were evaluated at admission. Clinical severity index was calculated at admission. Clinical and clinicopathological data were compared between survivors and non-survivors. Sixty-five dogs with acute pancreatitis were assessed. Clinical severity index ≥ 6.5 were associated with poor outcome ( P  = 0.0011). Serum urea and creatinine concentrations at admission were significantly lower in survivors than non-survivors ( P <  0.0001 and P  = 0.0002, respectively). Acute kidney injury was diagnosed in 17/65 dogs (26.2%) and was associated with poor outcome ( P <  0.0001). Oligo-anuria was associated with poor outcome ( P  = 0.0294). Increased clinical severity index and azotemia in dogs with acute pancreatitis were associated with an increased risk of mortality. Acute kidney injury may be a comorbidity of canine acute pancreatitis. The presence of oligo-anuria is associated with poor outcome.